A Case Study on Successful Ayurvedic Management of Fibromyalagia (AYUSHDHARA, 2022)
Fibromyalagia is mainly characterized by pain, fatigue, and sleep disruption, it is also characterized by tiredness, anxiety, depression, and disturbances in bowel functions, which can exhibit significant variation not only between different patients, but also in the same patient during the course of the disease. Management of FMS at the present time is very difficult as it has multiple etiological factors and psychological predispositions. Here is a case of 42 year old female patient suffering from fibromyalagia since 3 years. Excellent relief in patient’s symptoms was noted by treatment of 22 days of Ayurvedic drugs (Shaman) and therapies (Shodhan) on VAS, MAF and HAM-D scales before and after treatment, which clearly indicates the efficacy of Ayurvedic treatment in Fibromyalagia.